Teachers' expectations and undergraduates' use of information resources in completing continuous assessments - Upathissa, P.A.A.H.; Gamage, Ruwan (University of Colombo, 2025)
Continuous assessments (CAs) are a key component of undergraduate learning, requiring students to engage with diverse information resources. Previous studies have examined assignment types, resource usage, access methods, and challenges related to CAs. However, limited attention has been given to lecturers’ expectations of information use and the gaps between these expectations and students' practices. This study addresses this gap by investigating how undergraduates at a private university (coded as ABC University) in Sri Lanka use information resources for assignments as a type of CAs, and how this aligns with what lecturers’ value. The University provides undergraduate courses in three disciplines: Engineering, Computing, and Business. A mixed-method survey design was adopted with a non-probabilistic sample. The population comprised 1,410 undergraduates and 62 academic and academic support staff. A convenience sample of 100 students and 15 staff members responded to an online questionnaire. Six staff members were purposively selected for follow-up interviews for triangulation. In addition, reference lists of 29 assignment answers from all three disciplines underwent a bibliometric analysis. Across all faculties, lecturers confirmed the necessity of using formal academic sources such as journal articles, academic textbooks, and library databases in completing undergraduate assignments. However, findings revealed variations in sources used by students. Engineering students often relied on academically trusted sources such as e-journals, library databases, and textbooks, while Computing students depended heavily on web-based resources, AI tools, and code repositories. Business students demonstrated a mixed approach, incorporating e-books, AI tools, and practical resources. Across all disciplines, lecture notes, websites, and online tools are used frequently, with limited reliance on physical libraries or paid subscriptions. Key challenges reported by students included limited search skills, time constraints, difficulties in citing references and evaluating source credibility. The study highlights both alignment and gaps between student practices and lecturer expectations. Strengthening information literacy and targeted support is recommended.
Keywords: Academic and academic support staff; Access to information sources; Assignments; Continuous assessments; Information resources